2010
DOI: 10.1590/s1984-82502010000100002
|View full text |Cite
|
Sign up to set email alerts
|

Mucoadhesive drug delivery systems

Abstract: Drug actions can be improved by developing new drug delivery systems, such as the mucoadhesive system. These systems remain in close contact with the absorption tissue, the mucous membrane, releasing the drug at the action site leading to a bioavailability increase and both local and systemic effects. Mucoadhesion is currently explained by six theories: electronic, adsorption, wettability, diffusion, fracture and mechanical. Several in vitro and in vivo methodologies are proposed for studying its mechanisms. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
192
0
22

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(215 citation statements)
references
References 45 publications
1
192
0
22
Order By: Relevance
“…Morevover, the high surface-to-volume ratio displayed by nanoparticles increases drug loading capacity (de la Fuente et al, 2008a). Previous studies have demonstrated that nanoparticle contact with epithelial surfaces is maximised when they display a size within 50 and 500 nm (Desai et al, 1996;Jani et al, 1990) and a strongly positive zeta potential (Bogataj et al, 2003;Carvalho et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Morevover, the high surface-to-volume ratio displayed by nanoparticles increases drug loading capacity (de la Fuente et al, 2008a). Previous studies have demonstrated that nanoparticle contact with epithelial surfaces is maximised when they display a size within 50 and 500 nm (Desai et al, 1996;Jani et al, 1990) and a strongly positive zeta potential (Bogataj et al, 2003;Carvalho et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This formulation exhibited characteristics of dilatant and reopetics fluids because of the increase in viscosity with increasing shear stress. This behaviour can be explained by filling the space between the particles with increasing shear stress: the sorting of particles promotes an increase in volume, causing an increase in melt strength, i.e., the viscosity (Carvalho et al, 2010a).…”
Section: Determination Of Rheological Behaviormentioning
confidence: 99%
“…This formulation exhibited characteristics of dilatant and reopetics fluids because of the increase in viscosity with increasing shear stress. This behaviour can be explained by filling the space between the particles with increasing shear stress: the sorting of particles promotes an increase in volume, causing an increase in melt strength, i.e., the viscosity (Carvalho et al, 2010a).After the extracts were added to formulations H1E and H2E, no alteration was observed in the rheological behaviour of formulations. Thus, the addition of the extract did not influence the rheological behaviour of the formulations.…”
mentioning
confidence: 99%
“…Mucoadhesion is bond formation between pressure sensitive adhesive with biological substrate (mucosal layer). 2,3 In design and development of drug delivery systems mucoadhesive drug delivery has been considered as subject of great interest due to various merits. Prolongation of the residence time of the dosage form at the site of application by increasing intimate contact of the dosage form with the underlying absorption surface and leads to improved absorption properties with enhanced bioavailability of therapeutic agents is major quality of these systems.…”
Section: Introductionmentioning
confidence: 99%